The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.2147/ibpc.s12214
|View full text |Cite
|
Sign up to set email alerts
|

Integrated control of hypertension by olmesartan medoxomil and hydrochlorothiazide and rationale for combination

Abstract: Hypertension affects nearly one-third of all individuals in the US, yet one-half of all treated patients achieve blood pressure (BP) controlled to recommended goals. The percentage of patients with uncontrolled BP is likely to be much higher when considering the number of patients who are not even aware of their hypertensive state. Elevated BP is associated with increased risks of cardiovascular events and end-organ damage. Antihypertensive monotherapy is not always sufficient to achieve BP goals, and thus mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 52 publications
0
3
0
2
Order By: Relevance
“…4 Monotherapy for the treatment of HTN has shown to achieve the desired BP goals in only one third of patients, and hence combination therapy is essential for reduction in the risk of adverse vascular outcome by effective achievement of BP goals in majority of hypertensive patients, especially stage 2 HTN. 26,27 For combination with S (-) amlodipine, telmisartan was the preferred agent of choice by the physicians. The rationale for combining agents which block the reninangiotensin-aldosterone system (RAAS) and CCB is well established, and addition of an angiotensin receptor blocker (ARB) to CCB monotherapy has shown to ameliorate oedema by reducing the capillary bed pressure owing to its venodilatory action along with arteriolar dilatation.…”
Section: Discussionmentioning
confidence: 99%
“…4 Monotherapy for the treatment of HTN has shown to achieve the desired BP goals in only one third of patients, and hence combination therapy is essential for reduction in the risk of adverse vascular outcome by effective achievement of BP goals in majority of hypertensive patients, especially stage 2 HTN. 26,27 For combination with S (-) amlodipine, telmisartan was the preferred agent of choice by the physicians. The rationale for combining agents which block the reninangiotensin-aldosterone system (RAAS) and CCB is well established, and addition of an angiotensin receptor blocker (ARB) to CCB monotherapy has shown to ameliorate oedema by reducing the capillary bed pressure owing to its venodilatory action along with arteriolar dilatation.…”
Section: Discussionmentioning
confidence: 99%
“…Use of HCTZ alone causes volume contraction, which has been shown to cause an increase in RAS pathway activity to compensate. The synergistic addition of a RAS inhibitor to HCTZ blunts this physiological response to diuresis, thereby achieving volume contraction with decreased RAS activity [Punzi 2009[Punzi , 2011Punzi et al 2010].…”
Section: Discussionmentioning
confidence: 99%
“…It can also be used as initial therapy in those who need large reductions in systolic or diastolic BP to achieve goal BP 16,17. A recent review integrating the relevant approval studies for the fixed-dose combination of olmesartan and HCTZ with and without amlodipine found that the BP-lowering effect of the combination of olmesartan and HCTZ was superior to other combination therapies, and discussed a rationale for choosing HCTZ over another diuretic, ie, chlorthalidone, based on pharmacokinetic differences, clinical concerns, and trends in use 18. One of the largest studies tested the combination of olmesartan and HCTZ in 502 patients against placebo and the respective monotherapies, and found greater reductions in BP than with the individual components for all six dose combinations.…”
Section: Discussionmentioning
confidence: 99%